Konstruksi kekuasaaan politik melalui program charity show media televisi - Indra Setia Bakti; Khairul Amin (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2019)
As a newcomer, the Perindo Party seeks to implement a specific strategy in order to compete with other parties that have already existed in the Indonesian political contestation. One of these is charity show programs. The high rating and concern societies watching the lives of poor people in various charity programs show besides creating profits also become a means of political communication. When political actors control the media, it is clear that there are interests also communicated, including the political powers of the funnel to get support from voters. When the Perindo Party is declared, the "scent" that HT and his party would use the media under their control is very clear. These signals can also be observed from the dominance of HT’s trusted people in the MNC Group in the composition of the Central Management Board Center, the Assembly of the Union Party and the court of Perindo party. That mean a charity program not only gives a very big business profit, but also the political media communication, enhance social branding in front of audiences, and build a base of loyal voters from poor family beneficiaries. To finishing this paper, the author uses a descriptive qualitative approach. The data in this article sourced from observations, studies of literature, and other sources considered relevant and then analyzed by the exchange theory of Peter Blau.